Immunogenicity and safety of vaccination against seasonal influenza vaccine in patients with psoriatic arthritis treated with secukinumab. Issue 4 (22nd January 2020) - Furer, Victoria; Zisman, Devy; Kaufman, Ilana; Arad, Uri; Berman, Mark; Sarbagil-Maman, Hagit; Elias, Muna; Hadad, Amir; Paran, Daphna; Drori, Yaron; Friedman, Nehemya; Mandelboim, Michal; et al.
Abstract: Objective: To assess the immunogenicity and safety of vaccination against seasonal influenza in psoriatic arthritis (PsA) patients treated with secukinumab versus healthy controls (HC). Methods: PsA patients administered secukinumab for ≥3 months and HC received the Sanofi Pasteur vaccine composed of 3 antigens (H3N3, H1N1, and B) and underwent clinical and laboratory assessments on the day of vaccination and 4–6 weeks later. Immunogenicity of the vaccine was evaluated by hemagglutination inhibition assay against those 3 antigens. Responders to each antigen were defined by a 4-fold increase in the antigen titer or by seroconversion in patients whose baseline level was <1/40. Results: Thirty-two consecutive PsA patients treated with secukinumab for ≥3 months comprised the study group, 10 of whom received concomitant conventional synthetic disease-modifying drugs, mostly methotrexate. There were 17 age- and gender-matched HC (median age 48.5 years, 6 females). The geometric mean titers of each antigen increased significantly in both groups. The number of responders in each group was similar for H3N2 and H1N1, and significantly higher for B/Brisbane in the PsA group. The proportion of patients with a seroprotective level (a titer >1/40) was high and similar in both groups. There was no correlation between the response rate and age, gender, or selected parameters of disease activity (tender/swollen joint counts, Leeds enthesitis index, physician and patient global assessment, psoriasis area severity index, and C-reactive protein). No disease exacerbation was observed following the vaccination. No serious adverse effects were observed in both groups during the study period. Conclusion: Secukinumab treatment does not affect the humoral response to influenza vaccine of patients with PsA.